Promotion of healthy adipose tissue remodeling ameliorates muscle inflammation in a mouse model of sarcopenic obesity - Ge, Yunlin; Li, Siqi; Yao, Tao; Tang, Yuexiao; Wan, Qiangyou; Zhang, Xiaoli; Zhao, Jing; Zhang, Mingliang; Shao, Mengle; Wang, Lijun; Wu, Ying (Frontiers in Nutrition, 2023)
A large subset of elders is classified as having sarcopenic obesity, a prevalence of obesity in combination with sarcopenia which places an aging population at the risk of adverse health consequences from both conditions. However, its complex etiology has restrained the development of effective therapeutic strategies. Recent progress has highlighted that the mode by which adipose tissue (AT) remodels is a determinant of metabolic health in the context of obesity. Healthy AT remodeling confers metabolic protection including insulin-sensitizing and anti-inflammatory effects to non-adipose tissues including skeletal muscle. Here, we employed a doxycycline-inducible adipocyte Hif1a knockout system to evaluate the muscle-protective effects associated with HIF1inactivation-induced healthy AT remodeling in a model of sarcopenic obesity. We found that adipocyte HIF1 inactivation leads to improved AT metabolic health, reduced serum levels of lipids and pro-inflammatory cytokines, and increase of circulating adipokine (APN) in ovariectomized obese mice fed with obesogenic high-fat diet (HFD). Concomitantly, muscle inflammation is evidently lower in obese OVX mice when adipocyte HIF1 is inactivated. Furthermore, these protective effects against muscle inflammation can be mimicked by the administration of adiponectin receptor agonist AdipoRon. Collectively, our findings underscore the importance of AT metabolic health in the context of concurrent sarcopenia and obesity, and promotion of healthy AT remodeling may represent a new therapeutic strategy to improve muscle health in sarcopenic obesity.